A new incremental cycling cognitive-motor dual-task test to assess simultaneous sustained attention and neuromuscular fatigue in trained athletes - Goepp, T.; Hayes, M.; Hot, P.; Rupp, T. (Scandinavian Journal of Medicine & Science in Sports, 2025)
Cognitive performance during cognitive-motor dual-task (CMDT) varies with exercise intensity. According to the inverted-U theory, low-to-moderate intensity enhances cognition, but this remains unexplored in trained individuals who may better sustain cognitive performance at high intensities due to improved prefrontal cortex (PFC) homeostasis. Additionally, how sustained attention influences neuromuscular fatigue during whole-body CMDT is unclear. This study investigated both during incremental cycling using an innovative ergometer. Forty trained adults (30 males/10 females; 28.5 ± 7.4 years, 22.9 ± 2.2 kg·m-2) performed an incremental cycling test with a sustained attention Mackworth task. The protocol consisted of 3-min ramp stages (starting at 1 W·kg-1, +0.4 W·kg-1 per stage) until "extremely strong" perceived effort (Borg CR100, task-failure TF). At each stage, we assessed: Mackworth score, quadriceps isometric maximal voluntary contraction (IMVC), neuromuscular fatigue (peripheral: twitch force, Pt; central: voluntary activation, VA), PFC oxygenation (NIRS), and mental effort. Data were interpolated at 20%, 40%, 60%, and 80% of TF. Pt decreased linearly (-40.7% ± 15.1%, p < 0.001). VA declined from 40%TF (-1.5% ± 0.9%, p = 0.003) and worsened at 80%TF (-6.9% ± 2.4%, p < 0.001), alongside IMVC (-20.9% ± 8.9%, p < 0.001). PFC oxygenation dropped from 60%TF (-7.9% ± 2.2%, p < 0.001). Mackworth performance declined only at TF (-11.0% ± 6.7%, p < 0.001), associated with = 84% ± 7% HRmax. Sustained attention did not follow the inverted-U theory during incremental cycling in trained adults. Cognitive impairments were observed at very strong intensities, in correlation with PFC deoxygenation. Central fatigue emerged early, itself correlated with increased mental effort and cerebral deoxygenation.